2017
DOI: 10.1038/s41598-017-03033-z
|View full text |Cite
|
Sign up to set email alerts
|

Combining Catalytic Microparticles with Droplets Formed by Phase Coexistence: Adsorption and Activity of Natural Clays at the Aqueous/Aqueous Interface

Abstract: Natural clay particles have been hypothesized as catalysts on the early Earth, potentially facilitating the formation of early organic (bio) molecules. Association of clay particles with droplets formed by liquidliquid phase separation could provide a physical mechanism for compartmentalization of inorganic catalysts in primitive protocells. Here we explore the distribution of natural clay mineral particles in poly(ethylene glycol) (PEG)/dextran (Dx) aqueous two-phase systems (ATPS). We compared the three main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 67 publications
1
44
0
Order By: Relevance
“…Jauregi et al [11] could separate ampicillin and phenylglycine crystal mixture by selective interfacial partitioning in a water/alkanol biphasic system. Recently, Cakmak and Keating [12] reported that natural clays, which work as reaction catalysts, partitioned differently by their kind in PEG/DEX ATPS and showed slight increase of reaction rate in ATPS compared to that in buffer. Also, Deng et al [13] reported that PEG/DEX ATPS could separate Merrifield resins and N-methylimidazolium grafted Merrifield resins by controlling the ATPS compositions, graft ratio and different anions of resins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jauregi et al [11] could separate ampicillin and phenylglycine crystal mixture by selective interfacial partitioning in a water/alkanol biphasic system. Recently, Cakmak and Keating [12] reported that natural clays, which work as reaction catalysts, partitioned differently by their kind in PEG/DEX ATPS and showed slight increase of reaction rate in ATPS compared to that in buffer. Also, Deng et al [13] reported that PEG/DEX ATPS could separate Merrifield resins and N-methylimidazolium grafted Merrifield resins by controlling the ATPS compositions, graft ratio and different anions of resins.…”
Section: Discussionmentioning
confidence: 99%
“…We chose FT-IR microscopy [5] mainly because of its simplicity and minimal amount of sample needed, compared to other known methods. Among them, zeta potential measurement [12,17], vibrating sample magnetometry (VSM) [18], X-ray photoelectron spectroscopy (XPS) [17,19], and thermogravimetry [15] can be considered as other tools for confirmation of surface modification, which may provide more quantitative information on the degree of modification.…”
Section: Discussionmentioning
confidence: 99%
“…This has led severalg roups to describe such droplets as water-in-water (w/w) emulsions. Spherical colloidsw ith diameters typicallyg reater than 100 nm, including nanoparticles, [85,86] lipid vesicles [87,88] and protein clusters, [89] as well as high-aspect-ratio colloids, such as clays, [90] nanorods [91] or protein fibrils, [92] adsorb more effectively to interfaces with lows urface tension [92,93] and have therefore been used to stabiliseP EG/dextran aqueous two-phase systems (Figure 2D,E ), as well as complex coacervate droplets. Spherical colloidsw ith diameters typicallyg reater than 100 nm, including nanoparticles, [85,86] lipid vesicles [87,88] and protein clusters, [89] as well as high-aspect-ratio colloids, such as clays, [90] nanorods [91] or protein fibrils, [92] adsorb more effectively to interfaces with lows urface tension [92,93] and have therefore been used to stabiliseP EG/dextran aqueous two-phase systems (Figure 2D,E ), as well as complex coacervate droplets.…”
Section: Controlled Matter Exchangest Hrough Interfacial Membrane Assmentioning
confidence: 99%
“…[83] Although conceptually trivial,t he stabilisation of w/w emulsions by surface-actives peciesi st echnically challenging, due to the very low interfacial tensionsi nvolved (surfacetensions cales as thermal energy over the square of molecule size, [84] thus resulting in low values for the macromolecules involved in LLPS). Spherical colloidsw ith diameters typicallyg reater than 100 nm, including nanoparticles, [85,86] lipid vesicles [87,88] and protein clusters, [89] as well as high-aspect-ratio colloids, such as clays, [90] nanorods [91] or protein fibrils, [92] adsorb more effectively to interfaces with lows urface tension [92,93] and have therefore been used to stabiliseP EG/dextran aqueous two-phase systems (Figure 2D,E ), as well as complex coacervate droplets. [94,95] Membraneso btained after the interfacial assembly of such large colloidal objects are usually highly permeable to molecular and macromolecules, due to the large size of the pores created.…”
Section: Controlled Matter Exchangest Hrough Interfacial Membrane Assmentioning
confidence: 99%
“…However, in spite of all of this focus on lipid vesicles, primitive compartments need not necessarily be lipid bilayer vesicles, as there are many other model systems that could have afforded essentially the same properties as lipid vesicles, including amphiphilic peptide vesicles [104], cationic organic amphiphile membrane vesicles [87], inorganic chemical cells [105], oil-in-water microdroplets [69], coacervate [106][107][108] (Figure 4) and aqueous two-phase system [109,110] droplets, and even membraneless polyester microdroplets [111], each of which is important for not only biophysicists, but also materials scientists. We look forward to the further collaboration between these two fields in Japan and abroad not only for further elucidation of the assembly and dynamics of primitive compartments in the context of OoL research, but also perhaps for the development of new therapeutic tools or new discoveries about modern biological systems as well [46].…”
Section: Assembly and Co-assembly Of Primitive Compartmentsmentioning
confidence: 99%